2017
DOI: 10.1007/s00603-017-1338-4
|View full text |Cite
|
Sign up to set email alerts
|

Dilatancy Criteria for Salt Cavern Design: A Comparison Between Stress- and Strain-Based Approaches

P. Labaune,
A. Rouabhi,
M. Tijani
et al.

Abstract: International audienceThis paper presents a new approach for salt cavern design, based on the use of the onset of dilatancy as a design threshold. In the proposed approach, a rheological model that includes dilatancy at the constitutive level is developed, and a strain-based dilatancy criterion is defined. As compared to classical design methods that consist in simulating cavern behavior through creep laws (fitted on long-term tests) and then using a criterion (derived from short-terms tests or experience) to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 26 publications
(21 reference statements)
0
7
0
1
Order By: Relevance
“…Cependant, certains auteurs suggèrent que la perméation, observée lors de tests in situ dans les cavernes de sel, a été partiellement induite par la construction de la caverne elle-même, car de fortes contraintes déviatoires se sont développées dans une zone de roche perturbée (appelée DRZ) autour des cavernes [1,15]. Dans la zone de perturbation rocheuse, des dommages et une dilatation se produisent [16,17]. La perméabilité augmente en effet de plusieurs ordres de grandeur sous une charge déviatrice, ce qui entraîne un endommagement [14,[18][19][20].…”
Section: Résuméunclassified
See 2 more Smart Citations
“…Cependant, certains auteurs suggèrent que la perméation, observée lors de tests in situ dans les cavernes de sel, a été partiellement induite par la construction de la caverne elle-même, car de fortes contraintes déviatoires se sont développées dans une zone de roche perturbée (appelée DRZ) autour des cavernes [1,15]. Dans la zone de perturbation rocheuse, des dommages et une dilatation se produisent [16,17]. La perméabilité augmente en effet de plusieurs ordres de grandeur sous une charge déviatrice, ce qui entraîne un endommagement [14,[18][19][20].…”
Section: Résuméunclassified
“…However, some authors suggest that permeation, observed during in situ tests in salt caverns, had been partially induced by cavern construction itself, as high deviatoric stresses were developed in a disturb rock zone (denoted DRZ) around caverns [1,15]. In the DRZ, damage and dilatancy occur [16,17]. Permeability indeed increases by several orders of magnitude under deviatoric loading, which leads to a damage [14,[18][19][20].…”
Section: Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…Results Example (Labaune et al, 2018). In last decades, authors who research on stability and safety of caverns have focused on 3D numerical simulation using high-performance computers to understand the behavior of salt cavern in different condition.…”
Section: Factormentioning
confidence: 99%
“…In last decades, authors who research on stability and safety of caverns have focused on 3D numerical simulation using high-performance computers to understand the behavior of salt cavern in different condition. However, because of complexities of damage processes such as rock bursting and splitting, only using numerical methods (either continuum or discontinuum) does not always provide an accurate representation of the physical settings of underground engineering specially salt cavern (Labaune et al, 2018). Some of authors applied discontinuum -based numerical methods such as 3DEC, DDA PFC3D (Cundall, 1988;Wu et al, 2004;Cai et al, 2007) to simulate the failure processes, however, their primary limitation lies in their computational constraints and poor understanding of the true physical response under complex conditions.…”
Section: Factormentioning
confidence: 99%